The image of woman in the poetry of W.B. Yeats (1865-1939) - Kaplan, Gloria (Department of English Language and Literature, 2016)
The purpose of this study is to examine the development of W.B. Yeats's concept of woman as it is revealed in his poetry and to evaluate its literary treatment. It is generally accepted that women played an important part in Yeats's life and that they exerted a significant influence in various directions - a fact that is borne out by the numerous friendships and relationships with women throughout his lifetime. It is not sufficiently realized, however, that they provided him with both a powerful source of poetic inspiration and an important subject matter throughout his poetic career. Woman, as an object of contemplation and speculation, forms an integral part of the very stuff and fibre of Yeats's poetry, as is testified to by the range, depth and inclusiveness of his vision, which comprises not only the expression of his personal dreams and longings but a more far-reaching and penetrating study of women's relationship to society, history and ethics. It is surprising, therefore, that the significance of woman in Yeats's poetic development has been so scantily treated by Yeats's critics.